Territories of color: analysis of Raquira’s imaginary of color - Vargas Patiño, Janeth Milena (Universidad de Boyacá, 2018)
This paper describes the results from a stage of the Territories of color research project, which was conducted in Ráquira (Boyacá). Color imagined by the town’s inhabitants was studied on the basis of the chromatic relations they make when perceiving their environment and living in the place. Urban imaginaries related to affective, emotional and sensory loads were thus recognized. These findings allowed to create a graphic summary proposing the town’s characterization based on the tones identified. The project followed a qualitative methodological approach that employed a survey, applied to the population, along with a workshop targeting a local school’s students for the data collection. In addition to this primary information, specialized literature was also examined. It was evidenced how the analysis of color from the dweller’s perspective enables a reading of the place’s culture and promotes a dialogue with the community. In this way, it is possible to characterize cultural identity elements, fostering their recognition and appropriation.